Strategy for strengthening social capital for the geographical indication protection community of Arabica coffee: A case study in the South Tapanuli Regency, Indonesia - Puji Wahyu Mulyani; Yuliana Kansrini; Dwi Febrimeli (Universitas Lancang Kuning, 2022)
Arabica coffee is a strategic commodity in Indonesia, especially in the South Tapanuli Regency, where the population of Arabica coffee farmers is concentrated in this area; their coffee product is known for its unique tastes. This opportunity improves agricultural jobs for young millennials interested in coffee. This research aimed to determine the role of farmers’ institutional social capital in supporting Arabica coffee agribusiness and define the strategy used to strengthen social capital in the community to protect the geographical indications protection community (GIPC) of Arabica coffee in South Tapanuli Regency. The methodologies for this research were both descriptive and qualitative approaches. The research used 15 informants from GIPC. The data analysis techniques included data reduction, presentation, conclusion, and verification. Three components were found after analyzing the social capital of GIPC Arabica coffee Sipirok’s institution in supporting the growth of Arabica coffee agribusiness in South Tapanuli Regency; they were norms, trust, and social networking. Therefore, the coffee agribusiness development strategy in South Tapanuli Regency was to strengthen internal GIPC and increase administrators' and members' capacity to consensus or mutual agreement related to GIPC institutional governance.